"I Don't Want a Book That's Going to Make Me Sad or Stressed Out, Especially in This Day and Age": Fiction Reading (and Healing) in a Pandemic. Issue 1 (13th October 2021) - Cho, Hyerim; Lee, Wan‐Chen; Urban, Alex; Huang, Li‐Min; Long, Yi
Abstract: To understand the roles of fiction reading in mitigating readers' stress during the COVID‐19 pandemic, this study explores readers' motivations, preferences, and reading behaviors. Through an open‐ended online survey posted on social media platforms and an online reading community, the researchers collected 76 responses from adult fiction readers. Through qualitative coding, three prominent themes were identified: escapism, re‐reading behavior, and access and format. Readers actively escape into fictional worlds, often through re‐reading books, to cope with the pandemic. Also, cost and available channels of access shape readers' selection of fiction book format. These themes highlight elements of fiction reading that are pertinent to emotionally‐strained individuals, which can provide insight for reference and recommendation services. By advancing researchers' understanding of pleasure reading behaviors and the important selection criteria for fiction readers during stressful times, this study contributes to the body of knowledge in Readers Advisory (RA) and information behavior.